Análisis del empleo adecuado en los egresados de la carrera economía de la Universidad Laica Vicente Rocafuerte - Loor Troya, Bryan Ricardo (2022)
The issue of adequate employment has been approached from various angles, however, the evidence suggests that the contradictions remain latent in developed countries, in the Latin American region and in Ecuador, especially when it comes to the university educational offer in the labor market. Such has been the research interest with the aim of analyzing the situation of adequate employment among the graduates of the Economics career of the VICENTE ROCAFUERTE Lay University of Guayaquil, from which the results obtained with the monitoring of the mixed approach, type of descriptive research, and the application of a survey to said graduates are presented; all of which made it possible to describe the situation in relation to adequate employment among graduates, as well as to reveal the factors that affect obtaining adequate employment, through the formulations suggested by the ILO and ECLAC. With regard to young people who are in the process of graduating from higher education, they supposedly had to overcome fewer difficulties in their management and employability status; however, the results point to weak incomeknowledge and employment-profile relationships; difficult job search; and the incidence of factors such as income levels; hours of the working day; job instability; age and gender inequality; and, the lack of integrality in conceiving young people as policy subjects. Accordingly, the topic supports its relevance by the context studied that is a priority in the guidelines of international and national legal regulations.